2022
DOI: 10.1128/spectrum.00105-22
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Shotgun Sequencing of Endocervical, Vaginal, and Rectal Samples among Fijian Women with and without Chlamydia trachomatis Reveals Disparate Microbial Populations and Function across Anatomic Sites: a Pilot Study

Abstract: Chlamydia trachomatis is the primary cause of bacterial sexually transmitted infections worldwide, with a disturbing increase in annual rates. While there is a plethora of data on healthy and pathogenic vaginal microbiomes—defining microbial profiles and associations with sexually transmitted infections (STIs)—far fewer studies have similarly examined the endocervix or rectum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
21
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 81 publications
9
21
1
Order By: Relevance
“…The differences in C. trachomatis strains between the vagina and endocervix of the same individual confirm that these sites can be effectively sampled without cross-contamination. In addition, shotgun metagenomics from some of the same samples as in this study also revealed related but diverged communities at each site ( Bommana et al, 2022 ). Further, while the endocervix is the site of infection and secretions along with the infected cells flow into the vagina, the vaginal environment may promote unique pressures on the genomes that are then detected as noted above.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…The differences in C. trachomatis strains between the vagina and endocervix of the same individual confirm that these sites can be effectively sampled without cross-contamination. In addition, shotgun metagenomics from some of the same samples as in this study also revealed related but diverged communities at each site ( Bommana et al, 2022 ). Further, while the endocervix is the site of infection and secretions along with the infected cells flow into the vagina, the vaginal environment may promote unique pressures on the genomes that are then detected as noted above.…”
Section: Resultssupporting
confidence: 57%
“…Genomic (g)DNA was extracted from remnant Xpert CT/NG transport media for vaginal swabs and remnant M4 transport media (Thermo Fisher, South San Francisco, CA) for endocervical and rectal swabs as described previously ( Bowden et al, 2021 ). Briefly, 59 μl consisting of 50 μL lysozyme (10 mg/mL; MilliporeSigma, St. Louis, MO), 3 μl of lysostaphin (4,000 U/mL in sodium acetate; MilliporeSigma) and 6 μl of mutanolysin (25,000 U/mL; MilliporeSigma) was added to 200 μl of remnant transport media and incubated for 1 h at 37°C as described ( Bommana et al, 2022 ). The QIAamp DNA mini kit (Qiagen, California) was then used for DNA extraction, according to manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The differences in C. trachomatis strains between the vagina and endocervix of the same individual confirm that these sites can be effectively sampled without cross-contamination. In addition, shotgun metagenomics from some of the same samples as in this study also revealed related but diverged communities at each site (28). Further, while the endocervix is the site of infection and secretions along with the infected cells flow into the vagina, the vaginal environment may promote unique pressures on the genomes that are then detected as noted above.…”
Section: Participants With Samples From Three Anatomic Body Sites Fel...supporting
confidence: 64%
“…Besides Candida a plethora of other species compose the vaginal microbiome, their identity and abundance differing with the anatomic site (for example, prominent differences were observed between the cervix or the uterus), with age, habits or race [20][21][22]. Despite the interindividual variation, it is clear that the vaginal microbiome is dominated by lactobacilli with Lactobacillus iners, Lactobacillus crispatus, Lactobacillus jensenii and Lactobacillus gasseri being most abundant [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the interindividual variation, it is clear that the vaginal microbiome is dominated by lactobacilli with Lactobacillus iners, Lactobacillus crispatus, Lactobacillus jensenii and Lactobacillus gasseri being most abundant [23,24]. Perturbation of the vaginal microbiome was linked to adverse gynaecologic/obstetric outcomes including preterm birth [25], mucosal inflammation [26] or infections caused by HPV [27], HIV [28] or bacteria [22,29]. Studies examining the vaginal microbiome of asymptomatic women or of patients with diagnosed vaginal candidiasis obtained conflicting results: some reported decreased abundance of the lactobacilli population; others report only changes in the species profile (for example, unusual predominance of L. iners); and others don't report any alterations to the habitual lactobacilli-enriched flora [17,19,[30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%